Between Perceived Delays in Fund Disbursement and SOP Compliance: Financial Verification Practices at the Secretariat of the Sidoarjo Regency DPRD - Mohammad Aditya Putra Wardana; Rizky Nurhidayat Perdana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Financial management within the DPRD secretariat places verification officers in a strategic and challenging position. They are required to maintain compliance with regulations and Standard Operating Procedures (SOPs) as instruments of public accountability. On the other hand, they face operational pressure from the Council's Apparatus (AKD), which demands accelerated budget disbursement to support the implementation of institutional functions. This tension often gives rise to the perception that the finance unit is a performance impediment, even though actual work practices demonstrate a high level of prudence. This study aims to analyze the work dynamics of Document Verification Subdivision Staff in financial management at the Sidoarjo Regency DPRD Secretariat, with an emphasis on administrative discretion practices, structural limitations, and role expectations of the officers. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation studies, and analyzed thematically using the Street-Level Bureaucracy framework. The results indicate that administrative discretion among officers emerges as a rational response to regulatory ambiguity, time pressure, and demands for organizational efficiency. This study concludes that financial verification practices are a compromise between the normative design of policies and the actual capacity of the apparatus. Therefore, they need to be understood as a dynamic aspect of governance, not simply a matter of procedural compliance.